Privacy of blockchain-enabled Internet of Vehicles - Tan, Ke Xiang (Nanyang Technological University, 2022)
The recent rise in popularity of cryptocurrencies and their underlying blockchain technology has piqued the interest of the research community. The decentralised nature of blockchain technology brings about a multitude of benefits. This makes it an attractive option for integration into various existing technologies and concepts. The Internet of Vehicles is one example of such a notion. While research has been done to examine the security benefits a blockchain brings, more can be done to address the privacy concerns of blockchain integration. Hence, this project aims to address the privacy concerns in blockchain-based IoV by providing on-demand privacy guarantees. This project will mainly focus on the traffic management application of Internet of Vehicle environments. Customised privacy-preserving schemes will be designed and implemented to simulate and test their effectiveness. This will be done by employing a simulator (CityFlow) to simulate traffic flows and a smart contract to perform storage of road information on the blockchain. The implemented solutions will provide obfuscation of vehicular details through the usage of tokens and provide loose coupling between these tokens and their respective vehicles. These solutions will also harden the environment to malicious attacks. Encryption, authentication, and verification schemes will serve to reduce the attack surface and exploitable vulnerabilities on the system. Ultimately, these solutions seek to achieve a level of privacy and security.